The "Entrepreneurial Boss" Effect on Employees' Future Entrepreneurship Choices: A Role Model Story? - Vera Rocha; Mirjam C. van Praag (Institute for the Study of Labor (IZA), 2016)
Both organizational and sociological approaches in entrepreneurship research highlight the importance of social context in shaping individual preferences for entrepreneurship. An influential contextual factor that has not been studied in entrepreneurship research is one's boss at work. Do entrepreneurial bosses contribute to their employees' decisions to become entrepreneurs themselves? Using Danish register data of newly founded firms and their entrepreneurs and employees between 2003 and 2012, and employing methods that allow causal inferences, we show that entrepreneurial bosses indeed affect their employees' future entrepreneurship choices, especially if both boss and employee are female. We investigate two alternative underlying mechanisms that may shape the (female) boss' influence on (female) workers' entrepreneurship decisions. Our results consistently suggest that entrepreneurial bosses may act as role models for the entrepreneurship activities of their employees, especially between pairs of female bosses and female employees. We do not find any evidence on female bosses acting as "queen bees" at the workplace. Female entrepreneurial bosses may, thus, act as a lever to reducing the gender gaps in entrepreneurship rates.
Keywords: L26; J24; J16; 330; entrepreneurship; role models; gender gaps; female leadership